A sound approach: Exploring a rapid and non-destructive ultrasonic pulse echo system for vegetable oils characterization. (November 2019) - Yan, Jing; Wright, William M.D.; O'Mahony, James A.; Roos, Yrjö; Cuijpers, Eric; van Ruth, Saskia M.
Abstract: A rapid and non-destructive ultrasonic pulse echo system was developed for vegetable oils characterization. To understand the differences in the ultrasonic properties of the oils, physical traits, such as their viscosity and density, were related to the ultrasonic data. In turn, these physical traits were correlated with the fatty acid compositions of the oils. Eighty oil samples, including 30 extra virgin olive oil (EVOO), 15 refined olive oil, 15 pomace olive oil, 10 rapeseed oil, 5 sunflower oil and 5 peanut oil samples, were analysed for their sound properties, viscosities, densities and fatty acid compositions. It was observed that the ultrasonic velocity of EVOO decreased linearly with increase in temperature, the temperature coefficient of ultrasonic velocity in EVOO was −2.92 m·s −1 ·°C −1 . The ultrasonic velocity of EVOO (1453 ± 2 m/s) differed significantly from those of pomace olive oil and the oils of other botanical origin, but not from the velocity of refined olive oil. Ultrasonic velocity was positively correlated with the density and negatively correlated with the viscosity of the oils. The higher density and lower viscosity of the oils were in turn related to a higher unsaturation degree of the oils. Hence, oils with a higher proportion of unsaturated fat present higher densities and lower viscosities, which resulted in higher ultrasonic velocity values. Ultrasonic measurements allow rapid, non-destructive analysis, and this first application for characterization of these oils is promising. Graphical abstract: Unlabelled Image Highlights: A rapid and non-destructive ultrasonic pulse echo system was developed for oil characterization. The ultrasonic velocity of EVOO decreased linearly with increase in temperature. The ultrasonic velocity of EVOO differed significantly from nearly all other types of oils. Ultrasonic velocity was positively correlated with the unsaturation degree of the oils.